2011
DOI: 10.1093/hmg/ddr294
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of laminopathies among patients with metabolic syndrome

Abstract: Constitutional laminopathies, such as the Dunnigan familial partial lipodystrophy, are severe diseases caused by mutations in A-type lamins and share several features with metabolic syndrome (MS). In this study, we hypothesized that MS may be, in some cases, a mild form of laminopathies and use the abnormal cell nucleus phenotype observed in these diseases as a primary screening test in patients suffering from common MS. Nuclear shape and lamin A nucleoplasmic distribution abnormalities were systematically sea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(61 citation statements)
references
References 32 publications
1
58
0
2
Order By: Relevance
“…Nonetheless, recently, a heterozygous (c.1312C4T, p.Leu438Phe) mutation was identified in a patient affected with a metabolic syndrome. 36 In this patient, slight prelamin A accumulation was detected by immunofluorescence analyses in fibroblasts, associated with nuclear abnormalities. In this case, processing of prelamin A was not complete as demonstrated by ELISA.…”
Section: Pathogenicity Of Splice Site Mutationsmentioning
confidence: 64%
“…Nonetheless, recently, a heterozygous (c.1312C4T, p.Leu438Phe) mutation was identified in a patient affected with a metabolic syndrome. 36 In this patient, slight prelamin A accumulation was detected by immunofluorescence analyses in fibroblasts, associated with nuclear abnormalities. In this case, processing of prelamin A was not complete as demonstrated by ELISA.…”
Section: Pathogenicity Of Splice Site Mutationsmentioning
confidence: 64%
“…Similarly, Dutour et al showed that 10 out of 87 patients with common metabolic syndrome had morphological abnormalities in their cell nuclei suggestive of FPL type 2 [14]. Sequencing analysis revealed that 3 of these 10 patients carried previously unreported missense mutations in LMNA or ZMPSTE24, encoding a zinc metalloprotease which genetic variants are known to cause laminopathy [14].…”
Section: Diagnostic Approach To Lipodystrophymentioning
confidence: 96%
“…A study of 5000 ambulatory controlled diabetic patients found that among those with body mass index <27 m 2 /kg and high insulin requirements (>100 U/day), there were five subjects with previously unrecognized FPL [55]. Similarly, Dutour et al showed that 10 out of 87 patients with common metabolic syndrome had morphological abnormalities in their cell nuclei suggestive of FPL type 2 [14]. Sequencing analysis revealed that 3 of these 10 patients carried previously unreported missense mutations in LMNA or ZMPSTE24, encoding a zinc metalloprotease which genetic variants are known to cause laminopathy [14].…”
Section: Diagnostic Approach To Lipodystrophymentioning
confidence: 98%
“…In contrast, amino acids substitutions in the immunoglobulin-like fold that occur in striated muscle diseases are predicted to lead to significant overall disruption of its tertiary structure [4,5]. Various other mutations in LMNA have been reported in subjects with abnormalities in adipose tissue, insulin sensitivity and fat metabolism but without the typical Dunnigan-type familial partial lipodystrophy phenotype [48][49][50].…”
Section: Hj Wormanmentioning
confidence: 99%